2015
DOI: 10.3892/ol.2015.3999
|View full text |Cite|
|
Sign up to set email alerts
|

Association between the expression levels of TAZ, AXL and CTGF and clinicopathological parameters in patients with colon cancer

Abstract: Abstract.Colon cancer accounts for a large proportion of all the cancer -associated morbidities worldwide. Genetic analysis and stratification of patients based on survival may identify genetic signatures potentially useful for prognostic or treatment planning purposes. Previous studies have reported that the messenger (m)RNA expression levels of tafazzin (TAZ), AXL receptor tyrosine kinase (AXL) and connective tissue growth factor (CTGF) were able to predict the survival of patients with colon cancer in two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…The overexpression of TAZ in SiHa cells could enhance cell growth in vitro and in vivo , and reduced expression of TAZ in SiHa and HeLa cells could inhibit cell growth in vitro and in vivo (Figs 2 and 3). It has been previously reported that strong expression of the TAZ protein is related to rectal cancer development and RT response[16]. Our results in vitro and in vivo also support the hypothesis that TAZ is a tumor enhancer in cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The overexpression of TAZ in SiHa cells could enhance cell growth in vitro and in vivo , and reduced expression of TAZ in SiHa and HeLa cells could inhibit cell growth in vitro and in vivo (Figs 2 and 3). It has been previously reported that strong expression of the TAZ protein is related to rectal cancer development and RT response[16]. Our results in vitro and in vivo also support the hypothesis that TAZ is a tumor enhancer in cervical cancer.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, TAZ has been observed to be overexpressed in several tumors, including thyroid carcinoma[18], rectal cancer[17], and colon cancer[16], suggesting it may function as a promoter in tumorigenesis. However, to date, the expression and mechanism of the involvement of TAZ in cervical cancer have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our results, the overexpression of CTGF was associated with shorter overall survival in multiple colon cancer subgroups16. Likewise, high expression of FAP has also been described to lead to poor patient prognosis17.…”
Section: Discussionsupporting
confidence: 89%
“…Although multimodal and combining therapeutic approaches including surgical resection, radiotherapy, and chemotherapy have been employed in different tumor stages, the mortality with impairment of life quality of life is still rising. CRC is a heterogeneous disease and accumulation of multiple underlying causative genetic mutations such as serine/threonine‐protein kinase B‐Raf (BRAF) or Neuroblastoma RAS (NRAS) is seen as a molecular biological basis of colorectal cancer. However, the definitive identification of biological factors driving the progression of colon cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%